An Ultrasound Scoring Model for the Prediction of Intrapartum Morbidly Adherent Placenta and Maternal Morbidity: A Cross-Sectional Study - El-Haieg, Dahlia O.; Madkour, Nadia M.; Basha, Mohammad Abd Alkhalik; Ahmad, Reda A.; Sadek, Somayya M.; Ibrahim, Safaa A.; Sibai, Hoda; Mahdy, Entesar R.; Abd Elhady, Rasha R.; Mohamed, Elshaimaa Mohamed; Khamis, Mai E. M.; Azmy, Taghreed M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Objective To design an ultrasound scoring model for the prediction of the intrapartum morbidly adherent placenta (MAP) and maternal morbidity.Patients and Methods 114 females with singleton pregnancies ≥ 28 weeks of gestation referred for suspicion of MAP were included. All patients underwent examination by two-dimensional ultrasound with the color Doppler setting. Five signs were evaluated: the retroplacental echolucent space, placental lacunae, the hyperechoic uterine-bladder interface, retroplacental myometrium thickness, and subplacental, uterine serosa-bladder wall, intraplacental and bladder wall vascularity. We designed a score ranging from 0–8.5 points, including the five signs according to their odds ratios and evaluated its prediction for MAP and maternal morbidity.Results Using multivariate logistic regression, all ultrasound signs were significant dependent predictors for both MAP and maternal morbidity (myometrium thickness < 1 mm followed by lacunae ≥ 4 and lost retroplacental echolucent space). The only independent predictors for MAP were myometrium thickness < 1 mm and lacunae ≥ 4, while myometrium thickness < 1 mm and lost retroplacental echolucent space were predictive for maternal morbidity. The score showed a perfect agreement with MAP and a good one for maternal morbidity.Conclusion Application of the score we designed can improve the ultrasound diagnosis of MAP and the maternal outcome.
Keywords: morbidly adherent placenta; ultrasound score; maternal morbidity